Coupling Dynamics of Quantum Dots in a Liquid-Crystal-Tunable Microdisk Resonator - Förstner, Jens; Meier, Cedrik; Piegdon, Karoline; Declair, Stefan; Hoischen, Andreas; Urbanski, Mark; Meier, Torsten; Kitzerow, Heinz-Siegfried (Advances in Optical Sciences Congress)
We experimentally and theoretically investigate microdisk resonators with embedded quantum dots immersed in a liquid crystal in its nematic phase, showing the tunabililty of the photonic modes via external parameters like temperature or electric field.
Keywords: tet_topic_microdisk